Improving bearing capacity using tire-derived-geo-cylinder – a haul road case study in Jalan Sikar Penajam Paser - Tatag Yufitra Rus; Willy Susanto; Sulardi (Indonesian Geotechnical Journal, 2022)
This paper showcases a potential solution to improve soil bearing capacity using tire-derived-geo-cylinder (TDGC). TDGC uses used tires to provide confining pressure and tensile strength, hence improving the soil’s bearing capacity. The solution is applied for a haul road project on Jalan Sikar Penajam Paser. The site is frequently passed by large vehicles such as large trucks for the transportation of wooden logs and other heavy equipment. The tires used for TDGC are used tires of type LT245/75R16, which has a standard rim of 16 mm, a tire width of 248 mm, and an overall diameter of 780 mm. This category of tires has a load index of 1250-1600 kg. The load index is the value representing the tire's capacity to withstand load. The improvement in bearing capacity is evaluated using dynamic cone penetrometer (DCP) tests. In addition, the DCP tests were also used to interpret the Californian Bearing Ratio (CBR) values. The results show that without TDGC, the average CBR value is only 4.7%. In contrast, with TDGC, the average CBR increased to 17.2%, an increase of 265%. The CBR value obtained with TDGC places the soil into fair category for Subbase course. The average bearing capacity value obtained before TDGC was about 75 kN/m2 and with TDGC, the soil experienced a significant increase in bearing capacity value to 245 kN/m2. The increase of bearing capacity and CBR value from application of TDGC are due to the combination of the tires and stone fill. The tires provide tensile strength to resist lateral soil pressure as well as increased confining pressure, hence increasing the compressive strength.